Obligate Brominating Enzymes Underlie Bromoform Production by Marine Cyanobacteria. Issue 4 (16th March 2021) - Thapa, Hem R.; Agarwal, Vinayak
Abstract : Marine algae are prolific producers of bromoform (CHBr3 ). This naturally produced molecule is a potent environmental pollutant as it volatilizes into the atmosphere and contributes to depletion of the ozone layer in a manner akin to, and in magnitude similar to, man‐made chlorofluorocarbons. While phototrophs such as seaweeds, diatoms, and dinoflagellates are known sources of bromoform, additional as yet unknown biogenetic sources of bromoform exist in the oceans. Here, using halogenating enzymes as diagnostic genetic elements, we demonstrate that marine cyanobacteria also possess the enzymological potential for bromoform production. Using recombinantly purified vanadium‐dependent bromoperoxidases from planktonic and bloom‐forming marine cyanobacteria in in vitro biochemical assays, we reconstitute the enzymatic production of bromoform. We find cyanobacterial bromoform synthesizing enzymes to be obligate brominases possessing no chlorinating activities. These results expand the repertoire of marine biotic sources that introduce this pollutant in the atmosphere.